Underutilized Medicinal Species of Crambe L. of the Flora of Ukraine - Kalista, Mariia (Agrobiodiversity for Improving Nutrition, Health and Life Quality, 2017)
It was pointed out that 8 species of the genus Crambe L. are in the flora of Ukraine. All of them are subject of protection at the different levels, therefore they should be cultivated for their conservation. The species of the genus Crambe are mostly semirossette caudex perennial herbaceous polycarpic. Different representatives have inflorescences from 0.4 to 1.5–2.5 m length, which gives them a special decorative value. The chemical-biological features of these species show the necessity for their widespread introduction and cultivation in farming. They are promising for use in fodder, food, decorative and medicinal purposes. It was shown that cultivation of these species is easy and doesn’t need many investments of money. These plants have a significant ability to grow after mowing. Low temperatures of germination of seeds are most important adaptations to the cool early spring period, which is good for growing under weather condition of Ukraine. Seeds of Crambe species keep their viability for 5 years or more. The norm of sowing is 5 kg of seeds per hectare. These species is adapted very well to the lack of moisture. Most species of Crambe were tested as forage plant, they shows easy process of cultivation and reach yields. Growing them for medicinal purpose (to extract vitamins and very important for human health substances) is very perspective for farming, because they content linoleic and linolenic acids, vitamin C and B1, carotene, and Crambe koktebelica has the antioxidant activity. Three species are cultivated in vitro and biochemical composition of their in vitro plants was found out and it showed significantly high content of important substances for medicine.